ANALISIS FAKTOR YANG MEMPENGARUHI KEPUASAN KONSUMEN DITINJAU DARI KUALITAS PRODUK, HARGA, LOKASI, DAN KUALITAS PELAYANAN PADA COFFESHOP BELIKOPI NGANJUK - Ningrum, Fitri Ani Kusnia; Ernestivita, Gesty (Universitas Nusantara PGRI Kediri, 2023)
This research is motivated by the community's culture of drinking coffee which was developed by the younger generation and packaged to be more modern by creating a business in the field of selling coffee. Especially at the Belikopi Nganjuk coffee shop, which has many devotees from all walks of life. The purpose of this research is to find out how the influence of product quality, price, location and service quality in increasing customer satisfaction. The respondents of this study were consumers of Belikopi Nganjuk who were randomly selected as many as 50 respondents. The method used in this research is quantitative which uses a questionnaire and is processed using SPSS v.23. The result of this study is that product quality partially has a significant effect on customer satisfaction. Price partially has a significant effect on consumer satisfaction. Location partially has a significant effect on customer satisfaction, service quality partially has no significant effect on customer satisfaction, the four variables simultaneously influence customer satisfaction.